Exercise and Mindfulness-Based-Stress-Reduction: A Multidimensional Approach Towards Cancer Survivorship Care - Timothy F. Marshall (Journal of Basic & Applied Sciences, 2016)
Cancer survivors often experience a variety of physiological deficits resulting from cancer treatment such as reduced muscle strength, decreased range of motion and poor balance. Cancer survivors also commonly experience psychosocial side effects, such as anxiety, depression and fear of recurrence. Overall, it is common for cancer survivors to report a decrease in physical and emotional wellbeing and overall quality of life. Research suggests that improvements in physical health can be achieved through moderate intensity exercise such as light resistance training and moderate aerobic exercise in this population. Mindfulness-Based-Stress-Reduction (MBSR) programming utilizes various mind/body techniques that can reduce state anxiety levels, distress and depression. While cancer survivors face numerous physiological and psychological challenges, exercise interventions focus on physical health, while MBSR interventions focus on psychosocial health. The American Medical Association (AMA) recommends a patient’s care should include psychological, physiological, psychosocial and educational components, emphasizing the need for an integrated approach to cancer survivorship. Integrating exercise and MBSR interventions may serve to optimize the overall health and quality of life of a cancer survivor.